Исследование гетеронаносистем металл–полупроводник NixInSe (0001) - Galiy, P.V.; Nenchuk, T.M.; Ciszewski, A.; Mazur, P.; Yarovets’, I.R.; Dveriy, O.R. (Металлофизика и новейшие технологии, 2017)
Scanning tunnelling microscopy/spectroscopy (STM/STS) data show that InSe layered crystal intercalated with nickel is a heteronanosystem—InSe layer-packet that alternates with nickel at fine dispersed phase in the interlayer gap. For analysis of the degree of metallicity of cleavage surfaces, an array of STS data obtained in the current imaging tunnelling spectroscopy (CITS) mode is used. By significantly different behaviour of current–voltage curves for metal and semiconductor at localized points of surface analysis on the cleavage within the bias voltages that correspond to the band gap of the semiconductor, the method for the calculation of the relative metal concentration on the cleavage surface is proposed. The constraints for this method of the relative concentration estimates are analysed. As determined, the value of the nickel relative concentration in the interlayer gap for the NixInSe systems can be up to 2%, taking into account features of obtaining of the cleavage surfaces in the layered crystals. To establish the structural characteristics of the nickel, the STM analysis with high spatial resolution is used followed by the 2D FFT filtration and height profiling of image data. The analysis of corresponding revealed periodicities allows revealing formation of the two-dimensional square lattice of nickel on certain nanoscale areas of surface.